2021
DOI: 10.1039/d0sm01817a
|View full text |Cite
|
Sign up to set email alerts
|

Short intrinsically disordered polypeptide–oligonucleotide conjugates for programmed self-assembly of nanospheres with temperature-dependent size controllability

Abstract: A new type of thermoresponsive nanospheres was successfully developed by using a series of short intrinsically disordered polypeptide conjugated oligonucleotides as assembling building blocks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…sELP–ON conjugates were synthesized as previously described. , A CuSO 4 solution (1 mM, 5 μL) and a fresh aqueous solution of sodium l -ascorbate (2 mM, 5 μL) were added into a 1.5 mL Eppendorf tube. After the solution turned yellow and cloudy, an alkynyl-sELP solution (10 mg/mL, 30 μL, dissolved in dimethyl sulfoxide, DMSO), azido-oligonucleotide solution (100 μM, 30 μL), and a 50% (v/v) DMSO aqueous solution (200 μL) were added into the tube.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…sELP–ON conjugates were synthesized as previously described. , A CuSO 4 solution (1 mM, 5 μL) and a fresh aqueous solution of sodium l -ascorbate (2 mM, 5 μL) were added into a 1.5 mL Eppendorf tube. After the solution turned yellow and cloudy, an alkynyl-sELP solution (10 mg/mL, 30 μL, dissolved in dimethyl sulfoxide, DMSO), azido-oligonucleotide solution (100 μM, 30 μL), and a 50% (v/v) DMSO aqueous solution (200 μL) were added into the tube.…”
Section: Methodsmentioning
confidence: 99%
“…Elastin-like polypeptides (ELPs) are artificial intrinsically disordered proteins containing pentapeptide repeats (PR) of (Val–Pro–Gly–Xaa–Gly) N (VPGXG, N is the number of repeated units and X can be any amino acid except proline), which can perform temperature-dependent phase separation and undergo coacervation to form liquid-like droplets upon heating above lower critical solution temperature (LCST). However, short ELPs ( N < 7) gained less attention owing to the high LCST. Previously, our group has reported that the short ELP (sELP) ( N = 6)-conjugated oligonucleotides (sELP–ONs) could self-assemble into nanospheres upon duplex formation at a low concentration (100 nM), which exhibited nanoscaled shrinking and expansion by heating and cooling . Later, another sELP–ON was synthesized and used to assemble with a multihead DNA nanostructure to form disordered hybrids to enhance the hydrophobic interactions of sELPs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the free amine terminal end of the ELP was reacted with an Nhydroxysuccinimide-activated ON immobilized on the solid support and, subsequently, cleaved after conjugation. This ELP exhibits a T cp of 35 concentration. The resulting ON-b-ELP bioconjugate did not assemble into micelles, as the single ON strand was unable to stabilize the structure.…”
Section: ■ Introductionmentioning
confidence: 95%
“…Recently, the group of Qian and Yang conjugated several commercially available azido-terminated ON sequences (of 21 to 38 bases) to a short commercial hydrophobic ELP with the VPGFG sequence (MW = 476 g/mol) modified at the C -terminus by an aliphatic alkyne group. , A copper­(I)-catalyzed azide–alkyne cycloaddition reaction in water/DMSO mixtures afforded the diblock bioconjugates, which were extracted by excision of the electrophoresed SDS-PAGE gels. In their first work, amphiphilic (VPGFG) 6 - b -ON and (VPGFG) 6 - b -complementary ON bioconjugates (ON from 21 to 38 bases) were hybridized together and formed 55–60 nm diameter vesicles. The vesicles were found sensitive to temperature and shrunk upon an increase in temperature, consistent with other ELP systems .…”
Section: Introductionmentioning
confidence: 99%